Characteristics of the early stages of intravenous bisphosphonate-related osteonecrosis of the jaw in patients with breast cancer. (November 2014) - Matsuo, Akira; Hamada, Hayato; Kaise, Hiroshi; Chikazu, Daichi; Yamada, Kimito; Kohno, Norio
Abstract Objective. The clinical features of the early stages of bisphosphonate-related osteonecrosis of the jaw (BRONJ) in patients with breast cancer remain unclear. A retrospective cohort study was conducted of patients with breast cancer who received intravenous bisphosphonate (BP) treatment in a single center in order to clarify the status of the early stages of BRONJ. Materials and methods. A BRONJ oral monitoring program was established in 247 breast cancer patients given intravenous BP treatment at the institution. The differences in age, BP treatment period, number of remaining teeth, oral hygiene status, presence of regular oral monitoring and the existence of suspected BRONJ (stage 0) among eight BRONJ and 36 non-BRONJ subjects who completed oral examinations were then compared. Results. BRONJ was observed in 0.4% of subjects on the first visit to the oral surgery clinic and in 3.2% of subjects during the follow-up period. Logistic regression analysis revealed that the odds ratio for identifying patients with BRONJ during follow-up by the presence of stage 0 at first visit was 24.0 (95% confidence interval [CI] = 3.6–161.7). The area under the receiver operating characteristic curve for identifying subjects with BRONJ by the presence of stage 0 was 0.82 (95% CI = 0.63–1.00). Conclusion. The results suggest that patients with stage 0 BRONJ on the first visit may progress to advanced BRONJ during the follow-up period. The oral monitoring program may contribute to the early detection of BRONJ.